Elevation angle‐of‐arrival determination for a standard and a modified superDARN HF radar layout. Issue 6 (12th December 2013) - McDonald, Andrew J.; Whittington, James; de, Sebastien; Custovic, Edhem; Kane, Thomas A.; Devlin, John C.
<x xml:space="preserve">Abstract</x> [1] Calculations have been developed for the determination of elevation angle of arrival for a modified Super Dual Auroral Radar Network (SuperDARN) HF radar antenna layout consisting of dual auxiliary interferometer arrays: one behind and one in front of the main array. These calculations show that such a layout removes the 2π ambiguity or angle‐of‐arrival aliasing effect observed in existing SuperDARN HF radars. Ray tracing and simulation results are presented which show that there is significant potential for aliasing with existing SuperDARN radars and the standard interferometer algorithm under routine operating conditions.